Future air pollution in the Shared Socio-economic Pathways. (January 2017) - Rao, Shilpa; Klimont, Zbigniew; Smith, Steven J.; Van Dingenen, Rita; Dentener, Frank; Bouwman, Lex; Riahi, Keywan; Amann, Markus; Bodirsky, Benjamin Leon; van Vuuren, Detlef P.; Aleluia Reis, Lara; Calvin, Katherine; et al.
Highlights: New generation of global long-term air pollution scenarios guided by the narratives consistent with the past air pollution policy experience and SSP storylines. The future air pollutant trajectories indicate a wider range of outcomes than in previous global scenarios like RCP. Ambitious new air quality policies and efficient enforcement assured by state of the art technology and functioning institutions, as assumed in SSP1 and SSP5 driven narratives, allows achieving significant improvement of air quality. The new scenarios offer potential for further in-depth analysis at the global and regional level including both climate and air pollution studies. Abstract: Emissions of air pollutants such as sulfur and nitrogen oxides and particulates have significant health impacts as well as effects on natural and anthropogenic ecosystems. These same emissions also can change atmospheric chemistry and the planetary energy balance, thereby impacting global and regional climate. Long-term scenarios for air pollutant emissions are needed as inputs to global climate and chemistry models, and for analysis linking air pollutant impacts across sectors. In this paper we present methodology and results for air pollutant emissions in Shared Socioeconomic Pathways (SSP) scenarios. We first present a set of three air pollution narratives that describe high, central, and low pollution control ambitions over the 21st century. These narratives are then translated into quantitative guidance for use in integrated assessment models. The resulting pollutant emission trajectories under the SSP scenarios cover a wider range than the scenarios used in previous international climate model comparisons. In the SSP3 and SSP4 scenarios, where economic, institutional and technological limitations slow air quality improvements, global pollutant emissions over the 21 st century can be comparable to current levels. Pollutant emissions in the SSP1 scenarios fall to low levels due to the assumption of technological advances and successful global action to control emissions.